Brazil - Governance in Brazil's Unified Health System : Raising the Quality of Public Spending and Resource Management - World Bank (Washington, DC, 2012)
This report on governance in Brazil's unified health system assesses resource allocation and management, planning and budgeting functions, and budget execution at different levels of government for public expenditures on health services. The emphasis is on understanding the incentives generated for service providers, and the overall soundness of the accountabilities established in the public health services expenditure system. The analysis seeks to identify weaknesses of accountabilities for service provision that stem from the structure and process of intergovernmental and provider funding flows and related managerial practices. The paper draws on and enhances an accepted governance tool, public expenditure tracking, in both tracking funding and analyzing the governance and corresponding managerial challenges that impede effective public sector financing. The tracking instrument was applied to a sample of states, municipalities and healthcare facilities in the country in 2004.